APEC in the 21st Century - Miranti, Riyana; Hew Wei-Yan, Denis (Book collections on Project MUSE., 2004)
APEC is a unique organization that promotes economic cooperation in the Asia-Pacific region. It remains an informal intergovernmental organization that provides a useful platform for leaders, ministers, businessmen and experts to discuss regional issues on a regular basis. This book examines APEC's accomplishments in recent years and the challenges it faces in the new century. These challenges include the proliferation of Free Trade Agreements in the region and the implications of China's accession in the World Trade Organization.